Legendre Polynomials Used for the Approximation of Cylindrical Surfaces - Dariusz Janecki; Krzysztof Stępien (Communications - Scientific letters of the University of Zilina, 2005)
The paper deals with a concept of application of orthogonal Legendre polynomials for the approximation of cylindrical surfaces. It presents fundamentals of a mathematical model of such approximation. The theoretical considerations are supported by the results of the experimental verification of the developed concept.